Long-term care as contested acoustical space: Exploring resident relationships and identities in sound. Issue 1 (March 2020) - Graham, Megan E
As the global population ages, residential care facilities are challenged to create positive living environments for people in later life. Health care acoustics are increasingly recognized as a key design factor in the experience of well-being for long-term care residents; however, acoustics are being conceptualized predominantly within the medical model. Just as the modern hospital battles disease with technology, sterility and efficiency, health care acoustics are receiving similar treatment. Materialist efforts towards acoustical separation evoke images of containment, quarantine and control, as if sound was something to be isolated. Sound becomes part of the contested space of long-term care that exists in tension between hospital and home. The move towards acoustical separation denies the social significance of sound in residents' lives. Sound does not displace care; it emplaces care and the social relationships therein. Drawing upon ethnographic fieldwork in a Canadian long-term care facility, this article will use a phenomenological lens to explore how relationships are shaped in sound among residents living in long-term care. Ethnographic vignettes illustrate how the free flow of music through the care unit incited collective engagement among residents, reduced barriers to sharing social space and constructed new social identity. The article concludes that residents' relationships are shaped within the acoustical milieu of the care unit and that to impose acoustical separation between residents' living spaces may further isolate residents who are already at risk of loneliness.